Prohet Muhammad's (SAW) early life - saniyasnainKhan (china goodwordbooks, 2021)
Saniyasnain Khan's "Prophet Muhammad's Early Years" tells the story of Prophet Muhammad's life from his birth in Mecca to his early preaching, focusing on his childhood, adolescence, and the beginning of his prophethood. It covers his upbringing by his grandfather and uncle, his early experiences as a merchant, his marriage to Khadijah, and the first revelations of the Quran. The book emphasizes the spirit of his teachings and aims to provide young readers with lessons for their daily lives.